Effects of adrenergic-stimulated lipolysis and cytokine production on in vitro mouse adipose tissue–islet interactions - Morgana Barroso Oquendo; Estela Lorza-Gil; David Juarez-Lopez; Robert Wagner; Andreas L. Birkenfeld; Susanne Ullrich; Felicia Gerst (Scientific Reports, 2022)
Abstract Inflammatory cytokines and non-esterified fatty acids (NEFAs) are obesity-linked factors that disturb insulin secretion. The aim of this study was to investigate whether pancreatic adipose tissue (pWAT) is able to generate a NEFA/cytokine overload within the pancreatic environment and as consequence to impact on insulin secretion. Pancreatic fat is a minor fat depot, therefore we used high-fat diet (HFD) feeding to induce pancreatic steatosis in mice. Relative Adipoq and Lep mRNA levels were higher in pWAT of HFD compared to chow diet mice. Regardless of HFD, Adipoq and Lep mRNA levels of pWAT were at least 10-times lower than those of epididymal fat (eWAT). Lipolysis stimulating receptors Adrb3 and Npr1 were expressed in pWAT and eWAT, and HFD reduced their expression in eWAT only. In accordance, HFD impaired lipolysis in eWAT but not in pWAT. Despite expression of Npr mRNA, lipolysis was stimulated solely by the adrenergic agonists, isoproterenol and adrenaline. Short term co-incubation of islets with CD/HFD pWAT did not alter insulin secretion. In the presence of CD/HFD eWAT, glucose stimulated insulin secretion only upon isoproterenol-induced lipolysis, i.e. in the presence of elevated NEFA. Isoproterenol augmented Il1b and Il6 mRNA levels both in pWAT and eWAT. These results suggest that an increased sympathetic activity enhances NEFA and cytokine load of the adipose microenvironment, including that of pancreatic fat, and by doing so it may alter beta-cell function.